Legitimidade e credibilidade: impasses da política econômica do governo Goulart - Fonseca, Pedro Cezar Dutra (Estudos Econômicos (São Paulo), 2004)
Most of the literature on the Goulart Administration relates the low growth rates and rise of inflation in the period to structural reasons, while the economic policy is usually viewed as erratic and hesitant. In opposition to these theses, we attempt to restore the importance of the economic policy inside the conjuncture, showing its rationality which is manifested in the constant changing of ministers in the economic area. In order to do so, we use Barros credibility model and Max Webers legitimacy concept to re-establish the predicaments of the Administration and their reflections on the guidance of the economic policy.